Circumstellar disks. Issue 69 (10th September 2015) - Meilland, A.; Stee, Ph.
Abstract : Disks are very common structures found around stars of different masses and evolutionary status. In this chapter we will discuss the basic properties of disks and how interferometric observations can put constraints on their structure. The chapter is organized in three sections: geometry of disks, physical conditions and chemical composition, and kinematics.